On the absence of grounds for liability for the death of the Ukrainian flight MN 17 - Бєлкін, Леонід Михайлович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
On the basis of summarizing the positions of experts, and analysis of international aviation law, taking into account the «hybrid» tactics of the war of the Russian Federation against Ukraine, proved the adequacy actions of the Ukrainian aviation authorities regarding restrictions on flights of Civil Aviation of the Donetsk region in the period preceding the death of Flight MN17, and there were no grounds to establish responsibility for the deaths of Ukraine this flight. In accordance with paragraph a) of Art. 9 Convention on international civil aviation, signed at Chicago, on 7 december 1944 (Chicago Convention), each contracting State may, for reasons of military necessity or public safety, restrict or prohibit uniformly the aircraft of other States from flying over certain areas of its territory, provided that no distinction in this respect is made between the aircraft of the State whose territory is involved, engaged in international scheduled airline services, and the aircraft of the other contracting States likewise engaged. Such prohibited areas shall be of reasonable extent and location so as not to interfere unnecessarily with air navigation. Ukraine, on the basis of available information, the sequence increases the allowable minimum height of civil aviation in the skies over the Donetsk region. But Ukraine did not know and could not know about the plans of terrorists to transfer anti-aircraft missile complex «Buk». According to claim. 1 Art. 10 Convention for the suppression of unlawful acts against the safety of civil aviation (Concluded at Montreal on 23 September 1971), contracting States shall, in accordance with international and national law, endeavour to take all practicable measure for the purpose of prevent ing the offences mentioned in Article 1(such crimes relates, in particular, and the destruction of aircraft in service, including in flight). The authorities of the Russian Federation, aware of the preparation for the illegal firing of air targets with virtually controlled the territory of the Russian Federation, did nothing to prevent this crime. Mismatch Action Russian international aviation regulations created conditions that the Ukrainian side could not make an objective decision to close/not closing airspace in Donbas, because they do not know and could not know about the planned criminal use of powerful anti-aircraft missile complexes of illegal armed groups. On the basis of their actual jurisdiction over the pro-Russian militants controlled territories of the Russian Federation not only had to encourage the use of arms and right to prevent its use. Under these conditions, there are no legal grounds for the establishment of any liability for the death of the Ukrainian flight MN17.